The business model canvas approach in evaluating the business strategy of the urban traffic fashion store in Medan - Dalimunthe, Muhammad Sarwadin Ansori; Haryadi, Haryadi (Lembaga Riset Mutiara Akbar, 2026)
This study aims to analyze and design a business model for the Urban Traffic Fashion Store in Medan, which faces intense competition and does not yet have a written, conceptualized business model. This study uses a descriptive qualitative method with a Business Model Canvas (BMC) approach and SWOT analysis. Data collection was conducted through in-depth interviews with the owner, employees, distributors, and customers. The results show that Urban Traffic's current business model still operates based on instinct and focuses strongly on physical stores. The main strength of this business lies in its value proposition of curating up-to-date products at affordable prices and personal styling services. However, significant weaknesses were identified, namely manual stock management, a heavy reliance on Instagram channels, and a revenue stream that only comes from physical sales. Therefore, this study resulted in the design of a new hybrid and integrated business model, with the main proposals being the digitization of stock management, diversification of sales channels to e-commerce and TikTok Shop, and the addition of new revenue streams from digital sales and partnerships with content creators.